Method for producing recycled positive electrode active material
Patent Information
- Application Number
- JP2024053575
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-03-28
AI Technical Summary
【0007】 本発明の一側面によれば、結晶子サイズの大きなリサイクル正極活物質を得ることが可能なリサイクル正極活物質の製造方法を提供することができる。
Smart Images

Figure 0007634746000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]
[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for recycling (reproducing) rare metal components from waste battery materials of secondary batteries is required (for example, see Patent Document 1 below). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-34021 A Summary of the Invention [Problem to be solved by the invention]
[0004] From the viewpoint of recycling rare metal components in the positive electrode active material, it is conceivable to obtain a recycled positive electrode active material by subjecting the positive electrode active material obtained from waste positive electrodes to various treatments. In this case, from the viewpoint of obtaining excellent battery characteristics using the recycled positive electrode active material, it is required to obtain a recycled positive electrode active material with a large crystallite size.
[0005] An object of one aspect of the present invention is to provide a method for producing a recycled positive electrode active material, which is capable of obtaining a recycled positive electrode active material with a large crystallite size. [Means for solving the problem]
[0006] In some aspects, the present invention relates to the following items [1] to [8], etc. [1] A method for producing a recycled positive electrode active material, comprising the following steps: Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): A step of heating the mixture to a temperature equal to or higher than the melting start temperature of the activation treatment agent in the presence of oxygen at a flow rate of 0.020 L / min or more per 1 L of heating space to obtain a heated mixture. Step (3): recovering the heated positive electrode active material from the heated mixture. [2] The method according to [1], wherein the flow rate of the oxygen in the step (2) is 0.020 to 0.150 L / min. [3] The method according to [1] or [2], wherein the proportion of the oxygen in the atmospheric gas in the step (2) is 20% by volume or more and less than 30% by volume. [4] The method according to any one of [1] to [3], wherein in the step (2), the mixture is heated to 600 to 1000°C. [5] The method according to any one of [1] to [4], wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. [6] The method according to any one of [1] to [4], wherein the positive electrode active material contains a lithium compound, and the activation treatment agent contains at least one compound selected from the group consisting of a potassium compound and a sodium compound, and a lithium compound. [7] The method according to any one of [1] to [6], wherein the positive electrode active material contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg [8] The method according to any one of [1] to [7], wherein the positive electrode active material contains a compound represented by the following formula (A): Li 1+a M 2 b M 1 M T c O2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements excluding Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metallic elements excluding O and P, -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5 are satisfied.
Advantages of the Invention
[0007] According to one aspect of the present invention, it is possible to provide a method for producing a recycled cathode active material capable of obtaining a recycled cathode active material having a large crystallite size.
Modes for Carrying Out the Invention
[0008] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.
[0009] The method for producing a recycled cathode active material according to this embodiment includes the following steps. Step (1): A step of mixing a cathode composite material containing a cathode active material and an activation treatment agent containing one or more alkali metal compounds to obtain a mixture Step (2): A step of heating the mixture to a temperature equal to or higher than the melting start temperature (Tmp) of the activation treatment agent in the presence of oxygen at a flow rate of 0.020 L / min or more per liter of the heating space to obtain a heated mixture Step (3): A step of recovering the heated cathode active material from the heated mixture
[0010] According to the manufacturing method of the recycled positive electrode active material of this embodiment, it is possible to obtain a recycled positive electrode active material with a large crystallite size. According to the manufacturing method of the recycled positive electrode active material of this embodiment, it is possible to obtain a crystallite size of, for example, 60 nm or more (preferably, 80 nm or more, 85 nm or more, 90 nm or more, 95 nm or more, 100 nm or more, etc.) in the evaluation method described in the examples described later.
[0011] When the activation treatment agent comes into contact with the positive electrode active material, it is possible to activate the positive electrode active material and suppress deterioration of the crystal structure of the positive electrode active material (in some cases, it may also be possible to obtain a repair effect of the crystal structure). In particular, in step (2), the activation treatment agent is melted (dissolved) by heating the mixture before heating to a temperature equal to or higher than the melting start temperature of the activation treatment agent, and the contact between the activation treatment agent (activation treatment agent in a molten state) and the positive electrode active material is improved, thereby accelerating the activation of the positive electrode active material. In addition, when the mixture before heating contains a fluorine compound (a compound containing fluorine) derived from a binder and / or an electrolytic solution (for example, an electrolyte in the electrolytic solution), the fluorine component is stabilized as an alkali metal fluoride by contacting the molten activation treatment agent with the fluorine compound, thereby preventing the generation of corrosive hydrogen fluoride that may reduce the activity of the positive electrode active material. Since it is necessary to sufficiently remove components other than the positive electrode active material when obtaining a recycled positive electrode active material, in step (2), components other than the positive electrode active material may be oxidized and decomposed to generate acidic gases such as carbon dioxide. In addition, although an activation treatment agent is used in step (2), hydrogen fluoride may be generated as an acidic gas. If these acidic gases are present, the crystal structure of the positive electrode active material may deteriorate. On the other hand, according to the manufacturing method of the recycled positive electrode active material according to the present embodiment, the mixture containing the activation treatment agent is heated in the presence of oxygen at the above-mentioned specific flow rate, so that the carbon-containing material is sufficiently oxidized and decomposed, and the acidic gas is easily discharged outside the system. As a result, the effect of suppressing the deterioration of the crystal structure of the positive electrode active material can be suitably obtained, and therefore a recycled positive electrode active material with a large crystallite size can be obtained. However, the factors that allow a recycled positive electrode active material with a large crystallite size to be obtained are not limited to the above factors.
[0012] According to one aspect of the method for producing the recycled positive electrode active material of the present embodiment, it is possible to obtain excellent battery characteristics. For example, although the positive electrode active material may deteriorate due to use of the battery and the crystallite size of the positive electrode active material may become fine, according to one aspect of the method for producing the recycled positive electrode active material of the present embodiment, it is possible to recover the battery characteristics by recovering the crystallite size. According to one aspect of the method for producing a recycled positive electrode active material according to the present embodiment, it is possible to obtain excellent discharge rate characteristics (e.g., the discharge rate characteristics of a lithium ion battery), and in the evaluation method (discharge rate test: 5C) described in the examples below, it is possible to obtain a discharge capacity of, for example, 130 mAh / g or more (preferably, 135 mAh / g or more, 138 mAh / g or more, etc.). According to one aspect of the manufacturing method of the recycled positive electrode active material according to the present embodiment, it is possible to obtain an excellent discharge capacity retention rate (e.g., the discharge capacity retention rate of a lithium ion battery), and in the evaluation method described in the examples below, for example, a discharge capacity retention rate of 70% or more (preferably 80% or more, 85% or more, etc.) can be obtained. According to one aspect of the method for producing a recycled positive electrode active material according to the present embodiment, it is possible to obtain an excellent initial charge / discharge efficiency (e.g., the initial charge / discharge efficiency of a lithium ion battery), and in the evaluation method described in the examples below, it is possible to obtain an initial charge / discharge efficiency of, for example, 90% or more (preferably, 91% or more, 92% or more, etc.).
[0013] The recycled positive electrode active material according to the present embodiment is a recycled positive electrode active material obtained by the manufacturing method of the recycled positive electrode active material according to the present embodiment (a recycled positive electrode active material finally obtained by the manufacturing method of the recycled positive electrode active material according to the present embodiment). The recycled positive electrode active material obtained from a battery mixture or the like by using the manufacturing method of the recycled positive electrode active material according to the present embodiment can be reused in the same manner as an unused active material. A well-known method can be used as a method for manufacturing a positive electrode or a battery using the recycled positive electrode active material. The recycled positive electrode active material and its manufacturing method according to the present embodiment may be used for various batteries, non-aqueous electrolyte batteries (e.g., non-aqueous electrolyte secondary batteries), and lithium ion batteries (e.g., lithium ion secondary batteries). The recycled positive electrode active material according to the present embodiment may be a positive electrode active material for lithium batteries. The discharge capacity of the recycled positive electrode active material according to the present embodiment may be, for example, 150 mAh / g or more.
[0014] The crystallite size of the recycled positive electrode active material according to this embodiment may be in the following range. The crystallite size may be 60 nm or more, 80 nm or more, 85 nm or more, 90 nm or more, 95 nm or more, 100 nm or more, or 105 nm or more. The crystallite size may be 120 nm or less, 110 nm or less, 100 nm or less, 95 nm or less, 90 nm or less, or 85 nm or less. From these viewpoints, the crystallite size may be 60 to 120 nm, 60 to 110 nm, 60 to 100 nm, 80 to 120 nm, 80 to 110 nm, 80 to 100 nm, 100 to 120 nm, or 100 to 110 nm. The crystallite size can be measured by the method described in the examples, and can be calculated by the Scherrer formula using the diffraction peak in the X-ray diffraction spectrum using CuKα radiation as a radiation source. For the measurement of crystallite size, for example, "X-ray Structure Analysis - Determining the Atomic Arrangement -" (3rd Edition published on April 30, 2002, by Waseda Yoshio and Matsubara Eiichiro) can be referred to.
[0015] In this specification, the positive electrode active material that has undergone steps (1) to (3) is referred to as a "recycled positive electrode active material". The recycled positive electrode active material that has undergone steps (1) to (3) can be suitably used for manufacturing a positive electrode or the like. The manufacturing method of the recycled positive electrode active material according to this embodiment can include additional steps before and after steps (1) to (3). In this specification, the positive electrode active material that has undergone steps (1) to (3) and the additional steps thereafter is also referred to as a "recycled positive electrode active material". Examples of the additional steps other than steps (1) to (3) include a step of preparing a positive electrode mixture and a step of washing the positive electrode mixture, which are performed before step (1), and steps (4) and (5), which are performed after step (3), which are described below.
[0016] Hereinafter, each step in the method for producing a recycled positive electrode active material according to this embodiment will be described in detail.
[0017] (Positive electrode mixture preparation process) The method for producing a recycled positive electrode active material according to this embodiment may include, prior to step (1), a positive electrode mixture preparation step of preparing a positive electrode mixture containing a positive electrode active material.
[0018] The positive electrode mixture may contain a carbon-containing material in addition to the positive electrode active material, and may contain at least one selected from the group consisting of a binder, a conductive material, and an electrolyte. When the positive electrode mixture contains a binder, the particles of the positive electrode active material may be bound to each other by the binder. When the positive electrode mixture contains a binder and a conductive agent, the particles of the positive electrode active material and the conductive material may be bound to each other by the binder. The electrolyte is a component that is derived from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound derived from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).
[0019] [Cathode active material] Examples of the positive electrode active material include composite compounds containing one or more of the following elements as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten.
[0020] The positive electrode active material may be composed of only a single compound, or may be composed of a plurality of compounds.
[0021] From the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, it is preferable that the positive electrode active material contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
[0022] From the viewpoint of facilitating the production of a recycled positive electrode active material with a large crystallite size, the positive electrode active material preferably contains a compound represented by the following formula (A).
[0023] Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg; M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P; M T represents at least one element selected from the group consisting of Ni, Co, Mn, and transition metal elements excluding Fe, X represents at least one element selected from the group consisting of non-metallic elements excluding O and P, -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5 are satisfied.
[0024] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In from the viewpoint of easily obtaining a recycled cathode active material with a large crystallite size. Examples of X include F, S, Cl, Br, I, Se, Te, N, etc.
[0025] The cathode active material preferably contains a composite oxide containing at least Li and Ni from the viewpoint of easily obtaining a recycled cathode active material with a large crystallite size.
[0026] In the cathode active material, M 1 The molar fraction of Ni in is preferably 0.3 to 0.95 from the viewpoint of easily obtaining a recycled cathode active material with a large crystallite size.
[0027] The crystal structure of the cathode active material (for example, composite oxide) is not particularly limited, but a layered structure is preferable, and a hexagonal or monoclinic crystal structure is more preferable from the viewpoint of easily obtaining a recycled cathode active material with a large crystallite size.
[0028] The hexagonal crystal structure is P3, P3 1 P3 2 R3, P-3, R-3, P312, P321, P3 1 12, P3 1 21, P3 2 12, P3 2 21, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P6 1 P6 5 P62 , P6 4 , P6 3 , P-6, P6 / m, P6 3 / m, P622, P6 1 22, P6 5 22, P6 2 22, P6 4 22, P6 3 22, P6mm, P6cc, P6 3 cm, P6 3 mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P6 3 / mcm and P6 3 / mmc.
[0029] The monoclinic crystal structure is P2, P2 1 , C2, Pm, Pc, Cm, Cc, P2 / m, P2 1 / m, C2 / m, P2 / c, P2 1 It belongs to any one space group selected from the group consisting of C2 / c and C3 / c.
[0030] From the viewpoint of facilitating the production of recycled positive electrode active materials with large crystallite sizes, it is preferable that the crystal structure of the positive electrode active material belongs to the space group R-3m contained in a hexagonal crystal structure or the space group C2 / m contained in a monoclinic crystal structure.
[0031] The crystal structure of the positive electrode active material can be identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.
[0032] The particle size of the positive electrode active material in the positive electrode mixture is not particularly limited, but may be about 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments). A volume-based cumulative particle size distribution curve is created from the particle size distribution, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material.
[0033] There is no particular limitation on the content of the positive electrode active material in the positive electrode mixture.
[0034] [Binding material] Examples of the binder include thermoplastic resins, and specific examples thereof include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). One type of binder may be used alone, or two or more types may be used in combination.
[0035] The content of the binder in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.
[0036] [Conductive material] Examples of the conductive material include metal-based conductive materials such as metal particles; and carbon-based conductive materials made of carbon materials.
[0037] Specific examples of carbon-based conductive materials include graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers and carbon nanotubes).
[0038] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.
[0039] The specific surface area of the carbon material used as the carbon-based conductive material is 0.1 to 500 m 2 The carbon-based conductive material may have a specific surface area of 30 m 2 / g or more of carbon material, 2 / g or more, and 2 / g or more of carbon black, 2 / g or more, and 2 / g or more, and the specific surface area may be 30 m 2 In the case where an activation treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the rate of oxidation treatment of the carbon-based conductive material can be increased, and even a carbon material having a small specific surface area can be oxidized in some cases.
[0040] The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.
[0041] [Electrolytes and Solvents] An example of an electrolyte is LiPF 6 , LiBF 4 , LiClO 4 , LiN(SO 2 CF 3 ) 2 , LiN(SO 2 F) 2 , LiCF 3 SO 3 The content of the electrolyte contained in the positive electrode mixture is not particularly limited, but may be 0.0005 to 7 mass %.
[0042] The positive electrode mixture may contain a solvent derived from the electrolyte, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.
[0043] [Recovery of cathode mixture] The positive electrode mixture can be obtained by separating and recovering the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer.
[0044] The "scrap positive electrodes" may be positive electrodes recovered from discarded batteries, and waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. The discarded batteries may be used batteries, or unused but non-standard batteries. The waste positive electrodes may be the ends of positive electrodes generated during the manufacturing process of batteries, or non-standard positive electrodes. As the positive electrode composite, waste positive electrode composite not attached to a current collector (waste generated during the manufacturing process of the positive electrode composite) may also be used.
[0045] The waste positive electrode has a current collector which is a metal foil such as aluminum foil or copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.
[0046] Examples of a method for separating the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer include a method for mechanically peeling the positive electrode mixture layer from the current collector (e.g., a method for scraping the positive electrode mixture layer from the current collector), a method for penetrating a solvent into the interface between the current collector and the positive electrode mixture layer to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.
[0047] (Positive electrode mixture cleaning process) When the cathode mixture contains an electrolyte, the method for producing a recycled cathode active material according to the present embodiment may include a washing step (cathode mixture washing step) for removing at least a part (part or all) of the electrolyte from the cathode mixture after the cathode mixture preparation step. In the cathode mixture washing step, it is preferable to remove at least a part of the electrolyte from the cathode mixture by contacting the cathode mixture with an electrolyte washing solvent. Specifically, the cathode mixture containing the cathode active material and the electrolyte is contacted with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.
[0048] Solid-liquid separation is an operation for separating a slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.
[0049] The electrolyte cleaning solvent is not particularly limited. Examples of the electrolyte cleaning solvent include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.
[0050] The positive electrode mixture can be brought into contact with the electrolyte washing solvent in a known contact device for powder and liquid (for example, a stirring tank).
[0051] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, the positive electrode mixture and the electrolyte washing solvent are preferably stirred to obtain a slurry.
[0052] In the washing step of the positive electrode composite material, after solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is again brought into contact with the electrolyte washing solvent to obtain a slurry, and the slurry is again separated into a solid component and a liquid component. In the washing step of the positive electrode composite material, rinsing may be performed multiple times. The slurry concentration in the rinsing can be adjusted as desired. In the rinsing, the slurry can also be stirred as described above.
[0053] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material may change from a layered rock salt structure to a spinel structure. LiPF 6 +16LiMO 2 +2O 2 → 6LiF+Li 3 PO 4 +8LiM 2 O 4
[0054] Furthermore, when the activation treatment agent contains lithium carbonate, lithium may be consumed through the following reaction. LiPF 6 +4Li 2 CO 3 → 6LiF+Li 3 PO 4 +4CO 2
[0055] The separated solid component may be dried to remove the electrolyte washing solvent by reducing pressure and / or heating, if necessary. The heating temperature may be 50 to 200°C.
[0056] (Step (1): Activation treatment agent mixing step) Step (1) (activation treatment agent mixing step) is a step of mixing a positive electrode mixture containing a positive electrode active material (for example, a positive electrode mixture obtained in a positive electrode mixture washing step) with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture.
[0057] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods. The order in which the positive electrode mixture and the activation treatment agent are mixed is not particularly limited.
[0058] During mixing, it is preferable to carry out a pulverizing and mixing step using a mixer equipped with mixing media such as balls, which can improve mixing efficiency.
[0059] As a mixing method, dry mixing is preferred from the viewpoint of easy mixing. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.
[0060] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Co., Ltd.).
[0061] The activation treatment agent used in this step will be described in detail below.
[0062] [Activation treatment agent] The activation treatment agent contains one or more alkali metal compounds. From the viewpoint of further enhancing the activation effect of the positive electrode active material, the activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or the sodium compound.
[0063] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set in consideration of the type of alkali metal compound, the type of target positive electrode active material, etc., and is preferably 50 mass% or more, more preferably 70 mass% or more, and may be 100 mass% relative to the total mass of the activation treatment agent.
[0064] Of the alkali metals contained in the alkali metal compound, the concentration of at least one alkali metal selected from the group consisting of potassium and sodium can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.
[0065] Examples of alkali metal compounds that are components of the activation treatment agent include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, tungstates, etc. These can be used alone or in combination as components of the activation treatment agent.
[0066] Specific examples of suitable alkali metal compounds include: Hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH; LiBO 2 , NaBO 2 , K.B.O. 2 , RbBO 2 , CsBO 2 borate etc.; Li 2 CO 3 , Na 2 CO 3 , K 2 CO 3 , RbCO 3 , CsCO 3 etc. carbonates; Li 2 O, Na 2 OK 2 O, Rb 2 O, Cs 2 Oxides such as O; Li 2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2 Peroxides etc.; LiO2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2 etc. superoxide; LiNO 3 , NaNO 3 , KNO 3 , RbNO 3 , CsNO 3 Nitrates etc.; Li 3 PO 4 , Na 3 PO 4 , K 3 PO 4 , Rb 3 PO 4 , Cs 3 PO 4 Phosphates, etc.; Li 2 SO 4 , Na 2 SO 4 , K 2 SO 4 , Rb 2 SO 4 , Cs 2 SO 4 Sulfates, etc.; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; LiVO 3 , NaVO 3 , K.V.O. 3 , RbVO 3 , CsVO 3 vanadates, etc.; Li 2 MoO 4 , Na 2 MoO 4 , K 2 MoO 4 , Rb 2 MoO 4 , CsMoO 4 Molybdates, etc.; Li 2 WO 4 , Na 2 WO 4 , K 2 WO4 , Rb 2 WO 4 , CsWO 4 and the like tungstates.
[0067] From the viewpoint of further enhancing the activation effect of the positive electrode active material, the activation treatment agent can contain at least one compound selected from the group consisting of potassium compounds and sodium compounds, and a compound (excluding potassium compounds and sodium compounds) containing the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.
[0068] For example, when the positive electrode active material in the positive electrode mixture contains a lithium compound (a compound containing lithium, such as a lithium composite oxide), the activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds, and a lithium compound. Examples of suitable lithium compounds include LiOH, LiBO 2 , Li 2 CO 3 , Li 2 O, Li 2 O 2 , LiO 2 , LiNO 3 , Li 3 PO 4 , Li 2 SO 4 , LiCl, LiVO 3 , LiBr, Li 2 MoO 4 , Li 2 WO 4 etc.
[0069] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include an alkaline earth metal compound containing an alkaline earth metal element such as magnesium, calcium, barium, etc. The alkaline earth metal compound may be contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.
[0070] The content of compounds other than the alkali metal compound in the activation treatment agent may be less than 50 mass % of the total mass of the activation treatment agent.
[0071] The content of the activation treatment agent in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the mass of the positive electrode active material contained in the positive electrode mixture.
[0072] In the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent, when the number of moles of the positive electrode active material (for example, the compound represented by the above formula (A)) contained in the positive electrode composite is taken as 1, the number of moles of the alkali metal element in the alkali metal compound in the activation treatment agent may be 0.001 to 200 times.
[0073] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material from the positive electrode mixture can be reduced, and the treatment speed (oxidative decomposition treatment speed) of the carbon-based conductive material, binder, etc. can be increased. In addition, the effect of preventing the generation of corrosive gas in step (2) can be improved. Furthermore, the discharge capacity of the battery manufactured using the recycled positive electrode active material obtained by the manufacturing method of the recycled positive electrode active material according to this embodiment can be further increased.
[0074] At least one of the alkali metal compounds contained in the activation treatment agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. The pH of a solution obtained by dissolving an activation treatment agent containing such an alkali metal compound in pure water is greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."
[0075] By using an alkaline activation treatment agent, the generation of corrosive gas in step (2) can be further suppressed, and thus the discharge capacity of the battery manufactured using the recycled positive electrode active material obtained by the manufacturing method of the recycled positive electrode active material according to the present embodiment can be further increased. In addition, by using an alkaline activation treatment agent, the treatment speed of the carbon-based conductive material, the binder, etc. can be increased.
[0076] Examples of alkali metal compounds that exhibit alkalinity when dissolved in water include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, superoxides, etc. of alkali metals. Specific examples of such alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; 2 CO 3 , Na 2 CO 3 , K 2 CO 3 , RbCO 3 , CsCO 3 Carbonates such as LiHCO 3 , NaHCO 3 , K.H.C.O. 3 , RbHCO 3 , CsHCO 3 etc.; Li 2 O, Na 2 OK 2 O, Rb 2 O, Cs 2 Oxides such as Li 2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2 Peroxides such as LiO 2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2 The activation treatment agent may contain one or more alkali metal compounds that exhibit alkalinity when dissolved in water.
[0077] When the conductive material contained in the positive electrode composite material includes a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of step (2). Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."
[0078] The use of an activation treatment agent having such an oxidizing power is particularly effective in promoting the oxidation of conductive materials such as carbon-based conductive materials to carbon dioxide and in promoting the oxidation of binders such as hydrocarbon materials to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the recycled positive electrode active material obtained by the manufacturing method for the recycled positive electrode active material according to this embodiment. In addition, the effect of preventing the generation of corrosive gas in step (2) can sometimes be improved.
[0079] Examples of alkali metal compounds having the oxidizing power required to oxidize carbon-based conductive materials or hydrocarbon materials to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, molybdates, etc. Such alkali metal compounds may be used alone or in combination of two or more.
[0080] Specific examples of alkali metal compounds include Li 2 O 2 , Na 2 O 2 , K 2 O 2 , Rb 2 O 2 , Cs 2 O 2 Peroxides such as LiO 2 , NaO 2 , K.O. 2 , RbO 2 , CsO 2 Superoxides such as LiNO 3 , NaNO 3 , KNO 3 , RbNO 3 , CsNO 3Nitrates such as Li 2 SO 4 , Na 2 SO 4 , K 2 SO 4 , Rb 2 SO 4 , Cs 2 SO 4 Sulfates such as LiVO 3 , NaVO 3 , K.V.O. 3 , RbVO 3 , CsVO 3 vanadates such as Li 2 MoO 4 , Na 2 MoO 4 , K 2 MoO 4 , Rb 2 MoO 4 , CsMoO 4 and the like molybdates.
[0081] (Step (2): heating step) Step (2) (heating step) is a step of heating the mixture obtained in step (1) (hereinafter, sometimes referred to as the "mixture before heating") to a temperature (e.g., a holding temperature) equal to or higher than the melting start temperature (Tmp) of the activation treatment agent to obtain a mixture (hereinafter, sometimes referred to as the "mixture after heating"). In step (2), if the mixture before heating contains a binder, the molten activation treatment agent can contact the binder to improve the oxidative decomposition rate of the binder, and if the mixture before heating contains a carbon-based conductive material, the molten activation treatment agent can contact the carbon-based conductive material to improve the oxidative decomposition rate of the carbon-based conductive material. In step (2), if the activation treatment agent contains the same alkali metal as the positive electrode active material, the insufficient alkali metal can be supplied to the positive electrode active material.
[0082] In step (2), the mixture before heating is heated in the presence of oxygen at a flow rate of 0.020 L / min or more per 1 L of heating space (in an atmosphere containing oxygen at said flow rate). By setting the oxygen flow rate to 0.020 L / min or more, a recycled positive electrode active material with a large crystallite size can be obtained, and excellent discharge rate characteristics, discharge capacity retention rate, and initial charge / discharge efficiency can be obtained.
[0083] The flow rate of oxygen per 1 L of heating space (unit: L / min. Hereinafter, the units of various flow rates will be omitted in some cases) is 0.020 or more as described above, and may be in the following ranges from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency. The flow rate of oxygen may be 0.030 or more, 0.040 or more, 0.050 or more, 0.060 or more, 0.070 or more, 0.080 or more, 0.090 or more, 0.100 or more, 0.110 or more, or 0.120 or more. The oxygen flow rate may be 0.300 or less, 0.250 or less, 0.200 or less, 0.150 or less, 0.130 or less, 0.120 or less, 0.110 or less, 0.100 or less, 0.090 or less, 0.080 or less, 0.070 or less, 0.060 or less, or 0.050 or less. From these perspectives, the oxygen flow rates are 0.020~0.300, 0.020~0.200, 0.020~0.150, 0.020~0.120, 0.020~0.100, 0.020~0.080, 0.020~0.050, 0.030~0.300, 0.030~0.200, 0.030~0.150, 0.030~0.120, 0.030~0.100, 0.030~0.080, 0.030~0.050, 0.040~0.300, 0.040~0.200, 0.040~0.150, 0. 0.040 to 0.120, 0.040 to 0.100, 0.040 to 0.080, 0.040 to 0.050, 0.050 to 0.300, 0.050 to 0.200, 0.050 to 0.150, 0.050 to 0.120, 0.050 to 0.100, 0.050 to 0.080, 0.080 to 0.300, 0.080 to 0.200, 0.080 to 0.150, 0.080 to 0.120, 0.080 to 0.100, 0.100 to 0.300, 0.100 to 0.200, or 0.100 to 0.150.
[0084] In step (2), from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency, the mixture before heating may be heated in the presence of oxygen at the following flow rate (unit: L / min) per 1 L of heating space and 1 g of the mixture before heating (in an atmosphere containing oxygen at the said flow rate). The flow rate of oxygen is 5.0×10 -4 That's it, 6.0 x 10 -4 That's it, 7.0 x 10 -4 That's it, 8.0 x 10 -4 That's it, 1.0 x 10 -3 That's it, 1.2 x 10 -3 That's it, 1.5 x 10 -3 That's it, 1.8 x 10 -3 That's it, 2.0 x 10 -3 That's it, 2.5 x 10 -3 or more than 3.0 x 10 -3 The flow rate of oxygen may be 1.0×10 -2 Below, 9.0 x 10 -3 Below, 8.0 x 10 -3 Below, 7.0 x 10 -3 Below, 6.0 x 10 -3 Below, 5.0 x 10 -3 Below, 4.0 x 10 -3 Below, 3.5 x 10 -3 Below, 3.0 x 10 -3 Below, 2.5 x 10 -3 Below, 2.0×10 -3 Below, 1.8 x 10 -3 Below, 1.5 x 10 -3 Below, 1.2 x 10 -3 Less than or equal to 1.0 x 10 -3 From these perspectives, the flow rate of oxygen may be 5.0×10 -4 ~1.0×10 -2 , 5.0×10 -4 ~4.0×10 -3 , 5.0×10 -4 ~3.0×10 -3 , 5.0×10 -4 ~2.0×10 -3 , 5.0×10 -4 ~1.5×10 -3 , 1.5×10-3 ~1.0×10 -2 , 1.5×10 -3 ~4.0×10 -3 , 1.5×10 -3 ~3.0×10 -3 , 1.5×10 -3 ~2.0×10 -3 , 2.0×10 -3 ~1.0×10 -2 , 2.0×10 -3 ~4.0×10 -3 , 2.0×10 -3 ~3.0×10 -3 , 3.0×10 -3 ~1.0×10 -2 , or 3.0×10 -3 ~4.0×10 -3 It may be.
[0085] The flow rate of oxygen may be adjusted by supplying only oxygen (e.g., oxygen gas) or by supplying a mixture containing oxygen and other components (e.g., air containing oxygen and nitrogen). The flow rate of oxygen may be the amount of oxygen supplied to the heating space.
[0086] The proportion of oxygen (unit: volume %) in the atmospheric gas in step (2) may be in the following range based on the total volume of the atmospheric gas from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge-discharge efficiency. The proportion of oxygen may be 20% or more, 25% or more, 30% or more, 40% or more, 50% or more, more than 50%, 60% or more, 70% or more, 80% or more, or 90% or more. The proportion of oxygen may be 100% or less, less than 100%, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, less than 50%, 40% or less, 30% or less, less than 30%, 25% or less, or 20% or less. From these viewpoints, the proportion of oxygen may be 20 to 100%, 20% or more and less than 100%, 20 to 80%, 20 to 50%, 20 to 30%, 20% or more and less than 30%, 20 to 25%, 50 to 100%, 50% or more and less than 100%, or 50 to 80%.
[0087] In step (2), the mixture before heating may be heated in the presence of oxygen and nitrogen (in an atmosphere containing oxygen and nitrogen). This makes it easier to increase the crystallite size of the recycled positive electrode active material and to obtain excellent discharge rate characteristics. In step (2), the mixture before heating may be heated in an atmosphere not containing nitrogen.
[0088] In step (2), from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency, the mixture before heating may be heated in the presence of nitrogen at the following flow rate (unit: L / min) per 1 L of heating space (in an atmosphere containing nitrogen at the flow rate). The flow rate of nitrogen may be greater than 0, 0.030 or more, 0.050 or more, 0.060 or more, 0.070 or more, 0.080 or more, 0.090 or more, 0.100 or more, 0.150 or more, 0.200 or more, 0.250 or more, 0.300 or more, 0.350 or more, 0.400 or more, 0.450 or more, or 0.500 or more. The flow rate of the nitrogen may be 3.000 or less, 2.500 or less, 2.000 or less, 1.500 or less, 1.000 or less, 0.900 or less, 0.800 or less, 0.700 or less, 0.600 or less, 0.550 or less, 0.500 or less, 0.450 or less, 0.400 or less, 0.350 or less, 0.300 or less, 0.250 or less, 0.200 or less, 0.150 or less, or 0.100 or less. From these perspectives, the flow rate of nitrogen should be between 0 and 3.000, between 0 and 0.600, between 0 and 0.400, between 0 and 0.300, between 0 and 0.200, between 0 and 0.100, 0.050 to 3.000, 0.050 to 0.600, 0.050 to 0.400, 0.050 to 0.300, 0.050 to 0.200, 0.050 to 0.100, 0.070 to 3.000, 0.070 to 0.600, 0.070 to 0.400, 0.070 to 0.300, 0. 070 to 0.200, 0.070 to 0.100, 0.100 to 3.000, 0.100 to 0.600, 0.100 to 0.400, 0.100 to 0.300, 0.100 to 0.200, 0.200 to 3.000, 0.200 to 0.600, 0.200 to 0.400, 0.200 to 0.300, 0.300 to 3.000, 0.300 to 0.600, 0.300 to 0.400, 0.400 to 3.000, or 0.400 to 0.600.
[0089] In step (2), from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency, the mixture before heating may be heated in the presence of nitrogen at the following flow rate (unit: L / min) per 1 L of heating space and 1 g of the mixture before heating (in an atmosphere containing nitrogen at the said flow rate). The flow rate of nitrogen is greater than 0 and less than 1.0×10 -3 That's it, 2.0 x 10 -3 That's it, 2.5 x 10 -3 That's it, 3.0 x 10 -3 That's it, 4.0 x 10 -3 That's it, 5.0 x 10 -3 That's it, 6.0 x 10 -3 That's it, 7.0 x 10 -3 That's it, 8.0 x 10 -3 That's it, 9.0 x 10 -3 That's it, 1.0 x 10 -2 or more, or 1.2×10 -2 The flow rate of nitrogen may be 1.0×10 -1 Below, 5.0 x 10 -2 Below, 3.0 x 10 -2 Below, 2.0×10 -2 Below, 1.8 x 10 -2 Below, 1.5 x 10 -2 Below, 1.2 x 10 -2 Below, 1.0 x 10 -2 Below, 9.0 x 10 -3 Below, 8.0 x 10 -3 Below, 7.0 x 10 -3 Below, 6.0 x 10 -3 Below, 5.0 x 10 -3 Below, 4.0 x 10 -3 Below, 3.0 x 10 -3 Less than or equal to 2.5 x 10 -3 In view of these points, the flow rate of nitrogen may be greater than 0 and less than 1.0×10 -1 Below, over 0 2.0×10 -2 Below, over 0, 1.0×10 -2 Below, over 0 8.0×10 -3 Below, 0 over 5.0×10 -3 Below, over 0 3.0×10 -3 Below, 2.0×10 -3~1.0×10 -1 , 2.0×10 -3 ~2.0×10 -2 , 2.0×10 -3 ~1.0×10 -2 , 2.0×10 -3 ~8.0×10 -3 , 2.0×10 -3 ~5.0×10 -3 , 2.0×10 -3 ~3.0×10 -3 , 3.0×10 -3 ~1.0×10 -1 , 3.0×10 -3 ~2.0×10 -2 , 3.0×10 -3 ~1.0×10 -2 , 3.0×10 -3 ~8.0×10 -3 , 3.0×10 -3 ~5.0×10 -3 , 5.0×10 -3 ~1.0×10 -1 , 5.0×10 -3 ~2.0×10 -2 , 5.0×10 -3 ~1.0×10 -2 , 5.0×10 -3 ~8.0×10 -3 , 8.0×10 -3 ~1.0×10 -1 , 8.0×10 -3 ~2.0×10 -2 , 8.0×10 -3 ~1.0×10 -2 , 1.0×10 -2 ~1.0×10 -1 , or 1.0×10 -2 ~2.0×10 -2 It may be.
[0090] The flow rate of nitrogen may be adjusted by supplying only nitrogen (e.g., nitrogen gas) or by supplying a mixture containing nitrogen and other components (e.g., air containing oxygen and nitrogen). The flow rate of nitrogen may be the amount of nitrogen supplied to the heating space.
[0091] The ratio of nitrogen (unit: volume %) in the atmosphere gas in step (2) may be in the following range based on the total volume of the atmosphere gas from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge-discharge efficiency. The ratio of nitrogen may be 0% or more, more than 0%, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, more than 50%, 60% or more, 70% or more, more than 70%, 75% or more, or 80% or more. The ratio of nitrogen may be 80% or less, 75% or less, 70% or less, 60% or less, 50% or less, less than 50%, 40% or less, 30% or less, 20% or less, or 10% or less. From these viewpoints, the proportion of nitrogen may be 0 to 80%, more than 0% and not more than 80%, 20 to 80%, 50 to 80%, 70 to 80%, more than 70% and not more than 80%, 75 to 80%, 0 to 50%, more than 0% and not more than 50%, or 20 to 50%.
[0092] In step (2), from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency, the mixture before heating may be heated in the presence of oxygen and nitrogen at the following total flow rate (unit: L / min) per 1 L of heating space (in an atmosphere containing oxygen and nitrogen at the total flow rate). The total flow rate of oxygen and nitrogen may be more than 0.020, 0.050 or more, 0.070 or more, more than 0.070, 0.100 or more, 0.150 or more, 0.200 or more, 0.250 or more, 0.300 or more, 0.350 or more, 0.400 or more, 0.450 or more, 0.500 or more, 0.550 or more, or 0.600 or more. The combined oxygen and nitrogen flow rate may be 3.000 or less, 2.500 or less, 2.000 or less, 1.500 or less, 1.000 or less, 0.900 or less, 0.800 or less, 0.750 or less, 0.700 or less, 0.650 or less, 0.600 or less, 0.550 or less, 0.500 or less, 0.450 or less, 0.400 or less, 0.350 or less, 0.300 or less, 0.250 or less, 0.200 or less, or 0.150 or less. From these viewpoints, the total flow rate of oxygen and nitrogen is more than 0.020 and not more than 3.000, more than 0.020 and not more than 0.800, more than 0.020 and not more than 0.600, more than 0.020 and not more than 0.500, more than 0.020 and not more than 0.400, more than 0.020 and not more than 0.300, more than 0.020 and not more than 0.200, 0.100 to 3.000, 0.100 to 0.800, 0.100 to 0.600, 0.100 to 0.500, 0.100 to 0.400, 0.100 to 0.300, 0.100 to 0.200, 0.20 It may be 0 to 3.000, 0.200 to 0.800, 0.200 to 0.600, 0.200 to 0.500, 0.200 to 0.400, 0.200 to 0.300, 0.300 to 3.000, 0.300 to 0.800, 0.300 to 0.600, 0.300 to 0.500, 0.300 to 0.400, 0.400 to 3.000, 0.400 to 0.800, 0.400 to 0.600, 0.400 to 0.500, 0.500 to 3.000, or 0.500 to 0.800.
[0093] In step (2), from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency, the mixture before heating may be heated in the presence of oxygen and nitrogen at the following total flow rate (unit: L / min) per 1 L of heating space and per 1 g of the mixture before heating (in an atmosphere containing oxygen and nitrogen at the said total flow rate). The total flow rate of oxygen and nitrogen is more than 0 and less than 1.0×10 -3 That's it, 2.0 x 10 -3 That's it, 2.5 x 10 -3 That's it, 3.0 x 10 -3 That's it, 4.0 x 10 -3 That's it, 5.0 x 10 -3 That's it, 6.0 x 10 -3 That's it, 7.0 x 10 -3 That's it, 8.0 x 10 -3 That's it, 9.0 x 10 -3 That's it, 1.0 x 10 -2 That's it, 1.2 x 10 -2 or more, or 1.5 x 10 -2 The total flow rate of oxygen and nitrogen may be 1.0×10 -1 Below, 5.0 x 10 -2 Below, 3.0 x 10 -2 Below, 2.0×10 -2 Below, 1.8 x 10 -2 Below, 1.5 x 10 -2 Below, 1.2 x 10 -2 Below, 1.0 x 10 -2 Below, 9.0 x 10 -3 Below, 8.0 x 10 -3 Below, 7.0 x 10 -3 Below, 6.0 x 10 -3 Below, 5.0 x 10 -3 Less than or equal to 4.0 x 10 -3 In view of these points, the total flow rate of oxygen and nitrogen may be greater than 0 and less than 1.0×10 -1 Below, over 0 2.0×10 -2 Below, 0 over 1.5×10 -2 Below, over 0, 1.0×10 -2 Below, over 0 8.0×10 -3 Below, 0 over 5.0×10 -3 Below, 2.5 x 10-3 ~1.0×10 -1 , 2.5×10 -3 ~2.0×10 -2 , 2.5×10 -3 ~1.5×10 -2 , 2.5×10 -3 ~1.0×10 -2 , 2.5×10 -3 ~8.0×10 -3 , 2.5×10 -3 ~5.0×10 -3 , 5.0×10 -3 ~1.0×10 -1 , 5.0×10 -3 ~2.0×10 -2 , 5.0×10 -3 ~1.5×10 -2 , 5.0×10 -3 ~1.0×10 -2 , 5.0×10 -3 ~8.0×10 -3 , 8.0×10 -3 ~1.0×10 -1 , 8.0×10 -3 ~2.0×10 -2 , 8.0×10 -3 ~1.5×10 -2 , 8.0×10 -3 ~1.0×10 -2 , 1.0×10 -2 ~1.0×10 -1 , 1.0×10 -2 ~2.0×10 -2 , 1.0×10 -2 ~1.5×10 -2 , 1.5×10 -2 ~1.0×10 -1 , or 1.5×10 -2 ~2.0×10 -2 It may be.
[0094] The total flow rate of oxygen and nitrogen may be adjusted by supplying only oxygen (e.g., oxygen gas), may be adjusted by supplying only nitrogen (e.g., nitrogen gas), may be adjusted by supplying a mixture containing oxygen and other components (e.g., air containing oxygen and nitrogen), may be adjusted by supplying a mixture containing nitrogen and other components (e.g., air containing oxygen and nitrogen). The total flow rate of oxygen and nitrogen may be the total supply amount of oxygen and nitrogen supplied to the heating space.
[0095] The ratio of oxygen to nitrogen in the atmospheric gas in step (2) (oxygen / nitrogen: volume basis) may be in the following ranges from the viewpoint of easily obtaining a recycled positive electrode active material with a large crystallite size, easily obtaining excellent discharge rate characteristics, easily obtaining an excellent discharge capacity retention rate, or easily obtaining an excellent initial charge / discharge efficiency. The ratio of oxygen to nitrogen may be 0.25 or more, 0.30 or more, 0.50 or more, 0.80 or more, 1.00 or more, more than 1.00, 1.20 or more, or 1.50 or more. The ratio of oxygen to nitrogen may be 3.00 or less, 2.50 or less, 2.00 or less, 1.50 or less, 1.20 or less, 1.00 or less, less than 1.00, 0.80 or less, 0.50 or less, 0.30 or less, or 0.25 or less. From these perspectives, the ratio of oxygen to nitrogen may be 0.25 to 3.00, 0.25 to 2.00, 0.25 to 0.50, 0.25 to 0.30, 0.50 to 3.00, or 0.50 to 2.00.
[0096] Components other than oxygen and nitrogen may be present in the heating space, examples of such components include argon, carbon dioxide, etc.
[0097] In step (2), the mixture before heating can be heated in the heating space of the heating means. Examples of the heating means include, but are not limited to, heating furnaces such as gas furnaces, electric furnaces, infrared heating furnaces, plasma heat treatment furnaces, heavy oil furnaces, intermediate furnaces, hydrogen heat treatment furnaces, and induction heating furnaces. The heating furnace may be a batch furnace or a continuous furnace. The "heating space" is a space in which the mixture to be heated is accommodated, and may be a closed space or an open space having an opening for carrying in or out the mixture. In the heating space, an atmospheric gas may be supplied while discharging the atmospheric gas, and the volume of the heating space may be the volume from the supply part of the atmospheric gas to the discharge part in the heating space as the volume of the space in which the atmospheric gas can exist.
[0098] The "initiation temperature of melting of an activation treatment (Tmp)" refers to the lowest temperature at which a part of the activation treatment exhibits a liquid phase.
[0099] The melting start temperature of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, the temperature at which the DTA signal shows an endothermic peak in differential thermal analysis (heating rate 10°C / min) using 5 mg of the activation treatment agent is the melting start temperature of the activation treatment agent. When the activation treatment agent contains two or more compounds, the lowest temperature at which the DTA signal shows an endothermic peak is the melting start temperature of the activation treatment agent. The melting start temperature of the activation treatment agent may be the melting start temperature of the alkali metal compound.
[0100] The melting start temperature of the activation treatment agent may be 700° C. or less, 650° C. or less, 600° C. or less, or 550° C. or less. The melting start temperature of the activation treatment agent may be 150° C. or more, 200° C. or more, 250° C. or more, 300° C. or more, 350° C. or more, 400° C. or more, 450° C. or more, 500° C. or more, or 550° C. or more. From these viewpoints, the melting start temperature of the activation treatment agent may be 150 to 700° C., 150 to 650° C., 150 to 600° C., 300 to 700° C., 300 to 650° C., 300 to 600° C., 500 to 700° C., 500 to 650° C., or 500 to 600° C.
[0101] By mixing the positive electrode composite with the activation treatment agent, the melting start temperature of the activation treatment agent becomes lower than the melting point of the activation treatment agent. The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated.
[0102] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, the melting point of the activation treatment agent is determined as the temperature at which the DTA signal shows an endothermic peak in differential thermal analysis (heating rate 10° C. / min) using 5 mg of the activation treatment agent.
[0103] The heating temperature (temperature of the heating step) may be 100° C. or more, 200° C. or more, 300° C. or more, 400° C. or more, 500° C. or more, 550° C. or more, 600° C. or more, 650° C. or more, or 700° C. or more. The heating temperature may be 1500° C. or less, 1200° C. or less, 1000° C. or less, 900° C. or less, 850° C. or less, 800° C. or less, 750° C. or less, or 700° C. or less. From these viewpoints, the heating temperature may be 100 to 1500° C., 100 to 1000° C., 100 to 800° C., 400 to 1500° C., 400 to 1000° C., 400 to 800° C., 600 to 1500° C., 600 to 1000° C., or 600 to 800° C.
[0104] The holding time at the heating temperature may be 10 minutes to 24 hours. The heating temperature and holding time can be appropriately adjusted depending on the types and combinations of the components constituting the positive electrode mixture (positive electrode active material; alkali metal compound and other compounds contained in the activation treatment agent; conductive material; binder, etc.). The rate of temperature rise to the heating temperature is not particularly limited.
[0105] The heating temperature is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each compound alone by mixing multiple types of compounds. When the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is the melting point of the alkali metal compounds.
[0106] The pressure of the atmosphere in step (2) is not particularly limited, and may be atmospheric pressure, a reduced pressure atmosphere, or a pressurized atmosphere.
[0107] There are no particular limitations on the amount of the mixture before heating, the container that contains the mixture before heating, the layer thickness of the mixture before heating in the container, the method and position of supplying the atmospheric gas, and the like.
[0108] After the heating in step (2), the heated mixture can be cooled to any temperature (for example, about room temperature (25° C.: the same applies below)) if necessary.
[0109] (Step (3): Positive electrode active material recovery step) Step (3) (positive electrode active material recovery step) is a step of recovering the heated positive electrode active material from the heated mixture after step (2). In step (3), the heated positive electrode active material may be recovered by removing at least a part (part or all) of the alkali metal compound from the heated mixture.
[0110] The mixture after heating may contain, in addition to the heated positive electrode active material, components derived from the activation treatment agent (such as an alkali metal compound), undecomposed conductive material and binder, other undecomposed substances of the positive electrode mixture, etc. When the positive electrode mixture contains an electrolyte containing a fluorine component, the mixture after heating may contain a fluorine component derived from the electrolyte.
[0111] Examples of the method for separating and recovering the heated positive electrode active material from the heated mixture include a solid-liquid separation method in which the heated mixture is mixed with a solvent such as water to form a slurry and then separated into solid and liquid, and a vaporization separation method in which the heated mixture is heated to vaporize and separate components other than the heated positive electrode active material, etc. The solid-liquid separation step in which the solid-liquid separation method is performed will be described below.
[0112] [Step (3a): Solid-liquid separation step] Step (3a) is a step of mixing (contacting) the mixture after heating with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into a solid component and a liquid component. In order to separate and recover the heated positive electrode active material from the mixture after heating, the mixture after heating is mixed with a liquid containing water to form a slurry, and then separated into a solid component and a liquid component by solid-liquid separation.
[0113] The liquid used for slurrying is not particularly limited as long as it contains water. The amount of water in the liquid may be 50% by mass or more. In order to increase the solubility of water-soluble components or to increase the processing speed, a component other than water may be added to the liquid to adjust the pH.
[0114] Suitable examples of the liquid containing water include pure water, alkaline cleaning liquid, etc. Examples of the alkaline cleaning liquid include an aqueous solution of at least one anhydride or hydrate selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate. Ammonia can also be used as the alkali.
[0115] The slurry may contain a solid component mainly containing the positive electrode active material after heating and a liquid component containing a water-soluble component other than the positive electrode active material. The liquid component may contain an alkali metal component derived from the activation treatment agent, a fluorine component derived from the binder and / or the electrolyte (e.g., an electrolyte in the electrolyte), and the like.
[0116] The amount of liquid to be mixed with the heated mixture can be appropriately determined taking into consideration the amounts of each of the components contained in the heated mixture (the heated positive electrode active material, water-soluble components other than the positive electrode active material, etc.).
[0117] In step (3a), it is preferable to obtain a slurry by stirring the mixture after heating with a liquid containing water, which promotes dissolution of the water-soluble components.
[0118] The slurry is subjected to solid-liquid separation. Solid-liquid separation is an operation for separating the slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.
[0119] In step (3a), after the solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is contacted again with a liquid containing water to obtain a slurry, and the slurry is then separated again into a solid component and a liquid component. In step (3a), the rinsing may be performed multiple times. The slurry concentration in the rinse can be adjusted as desired.
[0120] (Step (4): Drying step) The method for producing a recycled positive electrode active material according to the present embodiment may include, after step (3), step (4) (drying step) of drying the wet material containing the solid component obtained in step (3a). Step (4) is a step of removing water from the wet material by exposing the wet material containing the solid component obtained in step (3a) to a heating and / or reduced pressure environment. When the wet material does not contain water, the method for producing a recycled positive electrode active material according to the present embodiment may not include step (4).
[0121] The heating temperature in step (4) may be 80° C. or more, 90° C. or more, or 100° C. or more from the viewpoint of facilitating removal of water. The heating temperature may be 900° C. or less, less than 900° C., 700° C. or less, 500° C. or less, 300° C. or less, 200° C. or less, or 100° C. or less. From these viewpoints, the heating temperature may be 100 to 900° C.
[0122] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It may be Pa.
[0123] (Step (5): Annealing (re-firing) step) The method for producing a recycled positive electrode active material according to this embodiment may include a step (5) (annealing step) of heat-treating a solid component (e.g., the solid component obtained in step (4)). Step (5) is preferably a step of heat-treating the solid component at less than 900°C. The method for producing a recycled positive electrode active material according to this embodiment does not need to include step (5).
[0124] The atmosphere for the heat treatment in step (5) is not particularly limited, but is preferably an oxygen-containing atmosphere such as air. The temperature for the heat treatment (e.g., holding temperature) may be, for example, 100°C or higher. The holding time for the heat treatment may be, for example, 1 minute to 24 hours. In particular, in step (5), heating at a temperature (e.g., holding temperature) of 350°C or higher for 0.1 to 5 hours is preferred. EXAMPLES
[0125] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0126] <Activation treatment agent mixing process> 90 parts by mass LiNi 0.33 Co 0.33 Mn 0.33 O 2 A positive electrode mixture (simulated mixture) was prepared by mixing 100 parts by mass of the positive electrode mixture (positive electrode active material), 3 parts by mass of PVdF (binder), 4 parts by mass of graphite (conductive material), and 3 parts by mass of carbon black (conductive material). 2 CO 3 10.3 parts by mass and K 2 CO 3 19.3 parts by mass were mixed to obtain mixture A (mixture before heating). The activation treatment agent had a melting start temperature of 550°C.
[0127] <Heating process> 40 g of mixture A was placed in an alumina container (square sagger, dimensions: 90 mm x 90 mm x 25 mm) and the container was placed in an electric furnace (heating space volume: 2.4 L). The layer thickness of mixture A in the container was 5 mm. Under atmospheric pressure, the temperature was raised from room temperature to 700 ° C at a heating rate of 300 ° C / hour, and mixture A was heat-treated (activated) at a holding temperature of 700 ° C for 6 hours (excluding the heating time). After natural cooling to room temperature, the mixture after heating was collected. In the heat treatment, air and / or oxygen gas was supplied to the heating space at the following flow rates while exhausting the atmospheric gas. The oxygen flow rate, nitrogen flow rate, and their total flow rates per 1 L of the heating space, as well as the ratio of oxygen and nitrogen in the atmospheric gas, are shown in Table 1. The oxygen flow rate and nitrogen flow rate were calculated assuming that the air was a mixture consisting of 20 volume % oxygen and 80 volume % nitrogen.
[0128] Comparative Example 1: Air 0.2 L / min Example 1: Air 0.5 L / min Example 2: Air 0.8 L / min Example 3: Air 1.1 L / min Example 4: Air 1.5 L / min Example 5: Air 0.25 L / min and oxygen gas 0.25 L / min Example 6: Oxygen gas 0.3 L / min
[0129] <Solid-liquid separation process> The heated mixture was pulverized and then mixed with water (5°C) to obtain a slurry with a concentration of 2% by mass. The slurry was stirred for 5 minutes at a stirrer speed of 500 rpm, and then filtered for 5 minutes to separate the slurry into solid and liquid components.
[0130] <Drying process> The solid component was dried under reduced pressure at 100° C. for 1 hour.
[0131] <Annealing process> The dried solid component was placed in an alumina container and the container was placed in an electric furnace. Under atmospheric pressure, the temperature was raised from room temperature to 700°C at a heating rate of 300°C / hour while exhausting the atmospheric gas and supplying air, and the solid component was heat-treated at a holding temperature of 700°C for 1 hour (excluding the heating time). After naturally cooling to room temperature, the recycled positive electrode active material was collected.
[0132] <Crystallite size measurement> First, an X-ray diffraction spectrum (diffraction pattern) was obtained by performing powder X-ray diffraction measurement (ray source: CuKα, measurement range of diffraction angle 2θ: 10 to 90°, sampling width: 0.02, scan speed: 4° / min). From this X-ray diffraction spectrum, the maximum diffraction peak within the range of 2θ = 18.5 ± 1° was determined. Bruker's D8 Advance was used as the X-ray diffractometer in the powder X-ray diffraction measurement. The half-width of the maximum diffraction peak was calculated, and the crystallite size was calculated using the Scherrer formula "L = Kλ / Bcosθ" (L: crystallite size, K: Scherrer constant, B: half-width of diffraction peak). The results are shown in Table 1.
[0133] <Production of positive electrodes> A mixture was obtained by mixing 92 parts by mass of the recycled positive electrode active material, 3 parts by mass of a binder (manufactured by Kureha Corporation, product number: PVdF#1100), and 5 parts by mass of carbon black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 52% by mass. The mixture was kneaded in an agate mortar to prepare a positive electrode mixture paste.
[0134] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 10.0 ± 0.2 mg / cm2. 2After applying the positive electrode composite paste so that the positive electrode was formed, the positive electrode was dried with hot air at 60°C for 1 hour, pressed at 0.5 MPa, and then vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of this positive electrode was 1.65 cm2. 2 It was.
[0135] <Battery manufacturing> The positive electrode, the electrolyte, the separator, and the negative electrode were combined to produce a coin-type battery (non-aqueous electrolyte secondary battery). The battery was assembled in a glove box in an argon atmosphere. The electrolyte was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 30:35:35, with LiPF 6 A solution in which the above was dissolved at a ratio of 1.0 mol / L was used. A laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used as the separator. Metallic lithium was used as the negative electrode.
[0136] <Battery characteristics> The above coin battery was subjected to the following charge / discharge test (25° C.). The results are shown in Table 1.
[0137] (Discharge rate characteristics) While changing the discharge current in sequence for each cycle, the battery was repeatedly charged at a constant current of 1C up to 4.3V, and then discharged at a constant current up to 2.5V. The discharge current was changed in the order of 0.2C, 0.5C, 1C, 2C, 3C, and 5C. The discharge capacity (unit: mAh / g) after discharging at 5C was measured.
[0138] (Discharge capacity maintenance rate) A constant current charge of 1C was performed up to a voltage of 4.3V, followed by a constant current discharge of 2C down to a voltage of 2.5V. This cycle was repeated 50 times, and the discharge capacities at the 1st and 50th cycles were measured. The ratio of the discharge capacity at the 50th cycle to the discharge capacity at the 1st cycle ([50 cycles / 1 cycle]×100%) was calculated as the discharge capacity retention rate.
[0139] (Initial charge / discharge efficiency) The battery was charged at a constant current of 0.2 C up to 4.3 V, and then discharged at a constant current of 0.2 C up to 2.5 V. The charge capacity and discharge capacity were measured, and the ratio of the discharge capacity to the charge capacity ([discharge capacity / charge capacity] × 100%) was calculated as the initial charge / discharge efficiency.
[0140] [Table 1]
Claims
1. The method includes the following steps: Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): Heating the mixture to a temperature equal to or higher than the melting start temperature of the activation treatment agent in the presence of oxygen at a flow rate of 0.020 L / min or more per 1 L of heating space to obtain a heated mixture. Step (3): Recovering the heated positive electrode active material from the heated mixture. In the step (2), the atmospheric gas is supplied to the heating space while being discharged.
2. 2. The method according to claim 1, wherein the flow rate of the oxygen in the step (2) is 0.020 to 0.150 L / min.
3. 2. The method according to claim 1, wherein the ratio of the oxygen in the atmospheric gas in the step (2) is 20% by volume or more and less than 30% by volume.
4. In the step (2), the mixture is heated in the presence of oxygen and nitrogen to a temperature equal to or higher than the melting start temperature of the activation treatment agent, The method for producing a recycled positive electrode active material according to claim 1 , wherein the flow rate of the nitrogen is more than 0 L / min and not more than 3,000 L / min per 1 L of the heating space.
5. The method according to claim 1, wherein the mixture is heated to 600 to 1000° C. in the step (2).
6. The method according to any one of claims 1 to 5, wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds.
7. the positive electrode active material contains a lithium compound, The method according to any one of claims 1 to 5, wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds, and a lithium compound.
8. The positive electrode active material comprises a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2. The manufacturing method according to any one of claims 1 to 5. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
9. The method according to any one of claims 1 to 5, wherein the positive electrode active material comprises a compound represented by the following formula (A): Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg; M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P; M T represents at least one element selected from the group consisting of transition metal elements excluding Ni, Co, Mn, and Fe; X represents at least one element selected from the group consisting of nonmetallic elements excluding O and P; The following conditions are satisfied: −0.4<a<1.5, 0≦b<0.5, 0≦c<0.5, −0.5<d<1.5, and 0≦e<0.5.
Citation Information
Patent Citations
Method and apparatus for recovering valuable metal in lithium secondary battery electrode material
JP2003206132A
Recycle processing method and device for lithium secondary battery electrode material
JP2005011698A
Processing method and recycling method of lithium battery
JP2005026088A
Method of recycling oxide-containing battery material from waste battery material
JP2010034021A
Method of manufacturing active material
JP2021140996A